A cross-sectional study of health profile of tuberculosis patients with special reference to air pollution exposure in central India - V., Abdul Kareem; Jiwane, Niwrutti (International Journal Of Community Medicine And Public Health, 2025)
Background: Exposure to air pollution worsens the health outcomes of tuberculosis (TB) patients, leading to severe symptoms, more comorbidities and poor treatment response. This study examines the health profile of TB patients concerning their residential air quality. To assess the health profile of TB patients with special reference to air pollution exposure. Methods: A cross-sectional study was conducted among 205 registered TB patients from four TB units under NTEP, residing in regions with moderate and poor Air Quality Index (AQI), between October 2023 and October 2024. Patients were randomly selected using the lottery method. Data were collected through household surveys, health records and anthropometric measurements. Statistical analysis was performed using EPI Info 7.2.6.0. Results: Of 205 patients, 55.1% were from moderate AQI and 44.8% from poor AQI regions. Males formed 66.3% and the most affected age group was 36–55 years. Over half (56.4%) belonged to the lower socioeconomic class. Previously treated cases and family history of TB were more frequent in poor AQI areas. Pulmonary TB was higher in poor AQI regions (78.2%) compared to moderate AQI areas (65.4%). Respiratory symptoms such as cough, sputum production, haemoptysis, chest pain, dyspnoea and allergy were significantly more common among patients from poor AQI regions. Conclusions: Poor air quality is strongly associated with severe respiratory symptoms and TB recurrence. The findings underscore the need for better air pollution control and targeted measures to reduce environmental risk among TB patients.